2023
DOI: 10.3389/fimmu.2022.1089621
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect and biological mechanism of exercise for rheumatoid arthritis: A mini review

Abstract: Rheumatoid arthritis (RA) is a common systematic, chronic inflammatory, autoimmune, and polyarticular disease, causing a range of clinical manifestations, including joint swelling, redness, pain, stiffness, fatigue, decreased quality of life, progressive disability, cardiovascular problems, and other comorbidities. Strong evidence has shown that exercise is effective for RA treatment in various clinical domains. Exercise training for relatively longer periods (e.g., ≥ 12 weeks) can decrease disease activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 129 publications
0
10
0
Order By: Relevance
“…It improves cholesterol metabolism by reducing body fat and weight, enhancing hormone and enzyme activity, and increasing 'good' high-density lipoprotein cholesterol [17]. Exercise also benefits cardiovascular health by reducing heart attack risks through antiatherogenic adaptations and myocardial regeneration [18], and aids autoimmune disease management by modulating immune cell functions and reducing inflammation [19]. Additionally, cardiovascular fitness, improved by exercise, is positively correlated with better hearing through enhanced inner ear blood circulation [20].…”
Section: Discussionmentioning
confidence: 99%
“…It improves cholesterol metabolism by reducing body fat and weight, enhancing hormone and enzyme activity, and increasing 'good' high-density lipoprotein cholesterol [17]. Exercise also benefits cardiovascular health by reducing heart attack risks through antiatherogenic adaptations and myocardial regeneration [18], and aids autoimmune disease management by modulating immune cell functions and reducing inflammation [19]. Additionally, cardiovascular fitness, improved by exercise, is positively correlated with better hearing through enhanced inner ear blood circulation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Further, patients with RA are worried that exercise aggravates joint inflammation and pain and accelerates joint injury; therefore, exercise is limited. Studies have confirmed that routine exercise in patients with RA has the benefits of relieving pain, improving muscle function, and delaying disability attacks and does not have harmful effects on joints ( 9 ). In addition to the factors that induce the occurrence and development of RA and associated declines in the quality of life of patients with RA, a series of complications caused by RA also seriously reduce the quality of life of patients with RA, such as fatigue, corneal diseases, and sleep disorders.…”
Section: Quality Of Life and Nursing Care Of Patients With Ra And Pmopmentioning
confidence: 99%
“…Clinically, joint pain, tenderness, and rigidity are often accompanied by immune osteoporosis. Irreversible joint injury gradually appears, with joint movement disorders and deformities occurring at later stages ( 9 ). Epidemiological investigations have shown that the total incidence of RA worldwide is 1–2%.…”
Section: Introductionmentioning
confidence: 99%
“…This condition typically leads to in ammation and bone destruction in multiple joints, resulting in long-term disability and signi cantly impacting patients' the quality of life [1][2] [3]. RA affects approximately 0.5-1% of the global population, making it a prevalent cause of severe disability [4] [5]. The exact cause of RA remains unclear, but it is believed to involve genetic [6], autoimmune [7], and environmental factors [8].…”
Section: Introductionmentioning
confidence: 99%